Early Evaluation of the Short Physical Performance Battery in Hospitalized Patients with Chronic Kidney Disease Predicts Long-Term Hospitalization - Takashi Amari; Eiji Kubo; Yota Kuramochi; Shota Onoda; Kyosuke Fukuda; Emi Yokoyama; Masami Kimura; Tomoyuki Arai (Diseases)
Background: The relationship between hospitalization duration and physical function in patients with chronic kidney disease (CKD) has not been thoroughly investigated. This study aimed to determine whether assessment of physical function one week after hospitalization can predict the length of stay in patients with CKD. Methods: A retrospective study was conducted on hospitalized patients with CKD who underwent rehabilitation between March 2019 and March 2020. Physical function was evaluated using the Short Physical Performance Battery (SPPB), grip strength, and Barthel Index and analyzed alongside clinical data. Results: The mean age of the participants was 73.4 ± 11.9 years, with 92% having stage G4 or G5 CKD. Multivariate analysis revealed that the SPPB (β = −0.33, p < 0.01) at one week after admission was significantly associated with the length of hospital stay (R2 = 0.11, p < 0.02). Notably, in the subgroup of patients who were transferred to other facilities, the SPPB alone showed a strong association with the length of stay (β = −0.66, p < 0.03, R2 = 0.23, p < 0.05). Conclusions: The SPPB score in the early stages of hospitalization for patients with CKD was found to be a significant predictor of the length of stay, even after considering the eGFR and the Charlson Comorbidity Index. These findings may contribute to optimizing inpatient management and rehabilitation strategies for patients with CKD.